The fight - Mailer, Norman . (Granada, 1975)
Norman Mailer's first person observations and story of the 1974 heavyweight-title boxing match between Muhammad Ali and George Foreman in Kinshasa, Zaïre. Mailer analyzes the fighters' moves as well as offering a close-up look at the fighters, trainers, hangers-on, the media and Zaire itself.